Using Intelligent Agents in Online Betting Management Systems - POPÎRLAN, Claudiu Ionut; GAVRILĂ, Laura; POPÎRLAN, Cristina (Journal of Advanced Research in Management; Vol 8 No 2 (2017): JARM Volume VIII Issue 2(16) Winter 2017DO - 10.14505//jarm. v8.2(16).04, 2018)
In this paper we present the possibility of integration intelligent agents in online betting strategy, in order to increase profitability. We proposed this approach for a betting management system and examined its usefulness in the online betting market. We also compared the proposed model against other most commonly used prediction methods.